Beriman di Tengah Sawit: Model Penghayatan Iman Umat di Tengah Sawit di Sakaq Lotoq, Kabupaten Kutai Barat, Kalimantan Timur Dalam Terang Iman Gereja Katolik - Siprianus Jegaut (Perspektif, 2024)
The focus of this study is to discuss "Belief in the Middle of Sawit: A model for the appreciation of the faith of the people in Sawit Sakaq Lotoq, West Kutai Regency, East Kalimantan in the Light of the Faith of the Catholic Church." Faith is one of the main resources in the journey of every Catholic. Faith directed towards the Triune God. God sows faith in the human heart with the aim that faith grows and develops, so that it produces fruit. Ways to strengthen faith are the celebration of the Eucharist, listening to the Word of God, devotional prayers and so on. However, the people in Sawit, especially in Sakaq Lotoq, are experiencing difficulties and limitations. This study aims to find a model for practicing the faith of Catholics in the midst of oil palm. The method used in this research is qualitative with two approaches, namely interviews and literature. This study found, first, that people's faith originates in the Triune God. Second, the people live their faith rooted in the spirit of the Triune God.